Trichoderma reesei xylanase 5 is defective in the reference strain QM6a but functional alleles are present in other wild-type strains - Ramoni, Jonas (Appl Microbiol Biotechnol, 2017)
Trichoderma reesei is a paradigm for the regulation and industrial production of plant cell wall-degrading enzymes. Among these, five xylanases, including the glycoside hydrolase (GH) family 11 XYN1 and XYN2, the GH10 XYN3, and the GH30 XYN4 and XYN6, were described. By genome mining and transcriptome analysis, a further putative xylanase, encoded by xyn5, was identified. Analysis of xyn5 from the genome-sequenced reference strain T. reesei QM6a shows that it encodes a non-functional, truncated form of XYN5. However, non-truncated orthologues are present in other genome sequenced Trichoderma spp., and sequencing of xyn5 in other T. reesei wild-type isolates shows that they harbor a putative functional xyn5 allele. In silico analysis and 3D modeling revealed that the encoded XYN5 has significant structural similarities to xylanases of the GH11 family, including a GH-typical substrate binding groove and a carboxylate pair in the active site. The xyn5 of wild-type strain TUCIM1282 was recombinantly expressed in a T. reesei strain with a (hemi)cellulase-free background and the corresponding protein purified to apparent homogeneity. The pH and temperature optima and the kinetic parameters of the purified XYN5 were pH 4, 50 °C, and V (max) = 2646 nkat/mg with a K (m) of 9.68 mg/ml. This functional xyn5 allele was used to replace the mutated version which led to an overall increase of the xylanolytic activity. These findings are of particular importance as GH11 xylanases are of high biotechnological relevance, and T. reesei is one of the main industrial producers of such lignocellulose-degrading enzymes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-017-8161-4) contains supplementary material, which is available to authorized users.